2020
DOI: 10.1016/j.nicl.2020.102403
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fronto-striatal volume in attention-deficit/hyperactivity disorder in two cohorts across the lifespan

Abstract: Highlights Reduced volume in frontal lobes, striatum, and their interconnecting white matter in ADHD. Cross-cultural and age-independent validity of the study including two independent cohorts. Data driven approach using ICA of whole-brain morphometry images.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Hence, a more detailed investigations of thalamic involvement in the pathophysiology of ADHD should take into account and specific analysis of such diverse nuclei (Battistella et al, 2017), so far still absent in the ADHD literature. Arguably, currently the most convincing effects with regard to thalamus role in ADHD, are found in the context of connectivity studies, pointing to the importance of fronto‐striatal circuits and their disruption in association to the symptomatology (Cupertino et al, 2019). Here, we corroborated these findings by embracing a different approach: we investigated the association between thalamocortical diffusivity and clinically assessed symptoms on the basis of individual differences in FA values.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a more detailed investigations of thalamic involvement in the pathophysiology of ADHD should take into account and specific analysis of such diverse nuclei (Battistella et al, 2017), so far still absent in the ADHD literature. Arguably, currently the most convincing effects with regard to thalamus role in ADHD, are found in the context of connectivity studies, pointing to the importance of fronto‐striatal circuits and their disruption in association to the symptomatology (Cupertino et al, 2019). Here, we corroborated these findings by embracing a different approach: we investigated the association between thalamocortical diffusivity and clinically assessed symptoms on the basis of individual differences in FA values.…”
Section: Discussionmentioning
confidence: 99%
“…But given that a previous study from our group using the same cohort found a positive impact of playing video games on intelligence 4 , it is unlikely that the striatal effect in this study might link to any negative cognitive effect. However, there is an association between smaller striatal volume and attention de cit hyperactivity disorder in children and adolescence 32,33 . Therefore, the present nding is a potentially serious observation that needs to be closely followed with longer periods of follow-up and associations to cognitive function and behavioural symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…But given that a previous study from our group using the same cohort found a positive impact of playing video games on intelligence 4 , it is unlikely that the striatal effect in this study might link to any negative cognitive effect. However, there is an association between smaller striatal volume and attention deficit hyperactivity disorder in children and adolescence 32, 33 . Therefore, the present finding is a potentially serious observation that needs to be closely followed with longer periods of follow-up and associations to cognitive function and behavioural symptoms.…”
Section: Discussionmentioning
confidence: 99%